Becoming the Ex-Wife - Gordon, Marsha,Parrott, Ursula (University of California Press, 2023)
The riveting biography of Ursula Parott-best-selling author, Hollywood screenwriter, and voice for the modern woman. Credited with popularizing the label
10.1525/9780520391550